Tinjauan Yuridis Pertanggungjawaban Hukum Atas Kesalahan Diagnosis Dokter yang Mengakibatkan Kematian Pasien - Triyanto Agung Praptono Wibowo (Pemuliaan Keadilan, 2026)
The increasing number of malpractice cases in Indonesia, particularly those related to misdiagnosis by medical practitioners, highlights the urgency of law enforcement in the health sector. This study aims to analyze the legal provisions and forms of physician liability for misdiagnosis resulting in patient death. The research employs a normative juridical approach with a library research method, using primary legal materials such as Law Number 17 of 2023 on Health, the Criminal Code (KUHP), and the Civil Code (KUHPerdata), as well as secondary legal materials including literature and legal health journals. The findings indicate that misdiagnosis proven to constitute professional negligence (culpa) may give rise to legal liability in three areas—criminal, civil, and administrative. Criminally, Article 440 of Law Number 17 of 2023 stipulates sanctions for medical personnel whose negligence causes serious injury or death (Republic of Indonesia, 2023). Furthermore, hospitals also bear responsibility under the doctrines of vicarious liability and hospital liability for the actions of medical practitioners under their supervision (Balubun, Simanjuntak, & Ginting, 2018). This research implies the need for a balanced legal protection framework between patients’ rights and the professional rights of medical practitioners, as well as the strengthening of medical supervision systems within healthcare institutions.